The New Mutants [videorecording (Blu-Ray)] - Boone, Josh, 1979-; Lee, Knate; Williams, Maisie, 1997-; Taylor-Joy, Anya, 1996-; Heaton, Charlie, 1994-; Braga, Alice; Hunt, Blu, 1995-; Zaga, Henry, 1993-; Beach, Adam, 1972-; Snow, Mark; Deming, Peter (20th Century Studios, 2020)
Five young people who demonstrate special powers are brought to a secret institution to undergo treatments they are told will cure them of the dangers of their powers. Invited by Dr. Cecilia Reyes to share their stories about when their powers first manifested, the five "patients" come to understand that they are in a class of people called mutants, who have historically been marginalized and feared.